Clinical Impact of Circulating Irisin on Classified Coronary Plaque Characteristics. (15th January 2020) - Hirayama, Kenshi; Ishii, Hideki; Kikuchi, Ryosuke; Suzuki, Susumu; Aoki, Toshijiro; Harada, Kazuhiro; Sumi, Takuya; Negishi, Yosuke; Shibata, Yohei; Tatami, Yosuke; Tanaka, Akihito; Murohara, Toyoaki
Abstract: Background: Myokines are hormones secreted by skeletal muscles during physical activity. Low myokine levels may contribute to metabolic dysfunction and cardiovascular disorders. Irisin, a newly identified myokine, has been the focus of recent research. The aim of the present study was to analyze the association between circulating irisin levels and tissue characteristics of nonculprit left main coronary artery (LMCA) plaques with the use of integrated backscatter (IB) intravascular ultrasound (IVUS). Methods: This observational study enrolled 55 Japanese patients following successful percutaneous coronary intervention for lesions in the left anterior descending arteries or left circumflex arteries. Circulating myokine levels, including myostatin, brain-derived neurotrophic factor, and irisin, were measured by an enzyme-linked immunosorbent assay. Tissue characteristics of LMCA plaque were evaluated by IB-IVUS. Results: Circulating irisin levels were negatively associated with percent lipid volume (%LV) [ r = −0.31 (95% CI, −2.52 to −0.21), P = 0.02] and positively associated with percent fibrous volume (%FV) [ r = 0.32 (95% CI, 0.22–2.20), P = 0.02]. The optimal cutoff value of circulating irisin for the prediction of lipid-rich LMCA plaques was 6.02 μg/mL [area under the curve = 0.713, P < 0.01 (95% CI, 0.58–0.85)]. Multivariate linear regression analysis identified circulating irisin levels as independent predictors for %LV and %FV of the LMCA [β = −0.29 (95% CI, −2.53 to −0.07), P = 0.04 and β = 0.30 (95% CI, 0.10–2.23), P = 0.03, respectively]. Conclusions: Circulating irisin levels are significantly associated with tissue characteristics of nonculprit LMCA plaques.